Swing and a miss: Reflections on the "voluntariness" of pleas in juvenile court. (October 2020) - Cabell, Jean J.; Marsh, Shawn C.
Abstract: Plea bargaining is a common tool in the U.S. justice system. When used appropriately and with defendant protections ensured, it can help keep an overloaded system operating smoothly and improve timely administration of justice. Adolescent defendants, however, present a unique population who often face plea bargain decisions before they are considered an adult in most other relevant contexts (e.g., voting). Because of developmental and social dynamics, adolescents could be more susceptible to influence from others, thereby accepting a plea bargain they do not actually fully endorse. This susceptibility introduces interesting considerations about how adolescents participate in plea bargain decisions – particularly regarding the degree to which they make the decision voluntarily and independently. This article employs a social psychological perspective to review some of the primary dynamics that judges and other legal actors should be aware of in assessing plea bargains made by juveniles, with a particular focus on the issue of "voluntariness". We conclude with nine recommendations for improving practice in adolescent plea bargain cases, as well as suggestions for future research on this relatively unexplored topic.